From Anxiety to Trust: A Transcendental Phenomenology of Dyadic Doctor–Patient Communication in Medical Decision–Making at an Indonesian Hospital - Tintin Tintin; Turnomo Rahardjo; Jamalullail Jamalullail; Mikhael Dua (Greenation Research & Yayasan Global Resarch National, 2026)
Effective doctor–patient communication remains a global problem: surveys across ten countries reveal wide perception gaps between doctors and patients, and in Indonesia 35% of patients report dissatisfaction with consultation communication, while prior research remains predominantly quantitative and overlooks the lived experience that constitutes the dyadic relationship. This study aims to explore the development of the doctor–patient communication relationship through the patient’s active involvement, the communication experiences of both parties, and the transcendental meaning of their dyadic relationship for patient centered care and the biopsychosocial model. Using an interpretive paradigm and a descriptive qualitative approach, Edmund Husserl’s transcendental phenomenology was applied through epoché, phenomenological reduction, imaginative variation, and synthesis of meaning to three purposively selected doctor–patient dyads—an internist, a pediatrician, and an obstetrician–gynecologist with their respective patients—at Hospital 123, Indonesia; data were collected through participant observation and in-depth semi-structured and unstructured interviews, and validated through triangulation of techniques, sources, and time. The results show that the relationship develops in stages, from digital pre-consultation information seeking through the orientation, affective exploration, affective, and stable levels, culminating in shared decision-making; the lived experience transforms patient anxiety into trust through the doctor’s empathic presence; and self-disclosure expands to include prayer, empathy, and respect, yielding a biopsychosocial–spiritual–cultural perspective. The study concludes that clinical communication is a humanizing encounter in which professional competence and empathy together restore the patient’s dignity, and it offers a four-level dyadic communication model for evaluating patient-centeredness in hospitals.